(untitled) (Sustainability in Debate, 2014)
With the premise of reducing emissions of greenhouse gases, international interest in biofuels has grown considerably in recent years. With the increasing demand and consequent expansion, the need to assess the impacts on the environment and society is unquestioned. Brazil, with large areas of arable and large current production of sugarcane, in addition to the added knowledge from decades of research and production of bioethanol, has the potential for expansion, but the consequences should be considered alongside to increased economic returns. For this, the application of the Barometer of Sustainability was made for two municipalities in the state of São Paulo: one with strong sugarcane expansion (Barretos), and another with stagnant production (Jaboticabal). The main objective was to identify the impacts based on the comparison of municipalities and identify causality in relation to the expansion of the culture under study. The application of sustainability barometer indicates a negative impact in the municipality with sugarcane expansion. In addition, the municipality without sugarcane expansion improves its human welfare performance against a stabilization of the municipality with expansion, indicating a relationship between the expansion of sugarcane and precariousness of human development.